Marketing 6.0 : the future is immersive - Kotler, Philip; Kartajaya, Hermawan, 1947-; Setiawan, Iwan (Hoboken, New Jersey : Wiley, 2024)
"In Marketing 6.0, the celebrated promoter of the "Four P's of Marketing," Philip Kotler, explains how marketers can use technology to address customers' needs and make a difference in the world. In a new age of metamarketing, this book provides marketers with a way to integrate technological and business model evolution with the dramatic shifts in consumer behavior that have happened in the last decade."--
Includes index.
Keywords: Marketing; Technology